Analysis of pre‐invasive lung adenocarcinoma lesions on thin‐section computerized tomography. (21st May 2014) - Xing, Yanfen; Li, Zhen; Jiang, Sen; Xiang, Wenjing; Sun, Xiwen
Abstract Introduction Recent studies have revealed a potential relationship between the presence of ground glass opacity (GGO) on regular computerized tomography (CT) and adenocarcinomas. Objectives To investigate features of pre‐invasive lung adenocarcinoma lesions on thin‐section CT. Methods We evaluated 59 cases of atypical adenomatous hyperplasia (AAH) and 35 cases of adenoma in situ (AIS) confirmed by histopathology. Comparison of thin‐section CT features, such as size, shape, margin, internal characteristics, and adjacent structures of pre‐invasive lesions were analyzed. Lesions were further classified to pure ground glass opacity (pGGO) and mixed ground glass opacity (mGGO). Differences were analyzed using Chi‐square or Fisher tests. Results There were significant differences in lobulation, spiculation, and bubble lucency between pGGO and mGGO (P < 0.05), while no differences in air bronchogram, pleural indentation, or vascular morphological changes were identified (P > 0.05). In the group of pGGO, AAH and AIS lesions did not differ significantly in size (P > 0.05), while significant differences were found with respect to lobulation, spiculation, pleural indentation, and vascular morphological changes (P < 0.05). In the group of mGGO, AAH and AIS lesions were significantly different with respect to size (P < 0.05), while no differences were found in lobulation, spiculation, bubble lucency, air bronchogram, or pleural indentation (P > 0.05). Only vascular morphological changes were significantly different between AAH and AIS lesions (P < 0.05). Conclusion The features of thin‐slice CT of AAH and AIS reflected the corresponding morphological changes from AAH progressing to AIS or adenocarcinoma.